Risky Business: Writing the Personal - Wearne, Heather (LiNQ (Literature in North Queensland), 2016)
My mother once told me that the world was no place for her stories. I knew from other sources that she could be right: that it is not the way of our culture to inscribe the lives of ordinary domesticated women into texts of cultural significance. I have written a biography of my mother Audrey Wearne. It is defiant of what was once thought about biography and women's lives and important matters of (H)istory and (C)ulture. It is a story of culture and its future becomings: as Aud becomes the subject of my work, the culture in which this story will reside becomes a thing it has never been: a place for her story.